Characterization of Cantal and Salers Protected Designation of Origin Cheeses Based on Sensory Analysis, Physicochemical Characteristics and Volatile Compounds - Cécile Bord; Louis Lenoir; Julie Benoit; Delphine Guérinon; Gilles Dechambre; Christophe Chassard; Christian Coelho (Applied Sciences)
In this work, the aim was to characterize and differentiate two Protected Designation of Origin (PDO) semi-hard French cheese categories (Salers and Cantal cheeses) by focusing on their sensory, biochemical and volatile characteristics. A total of twelve cheeses, including six Cantal and six Salers cheeses, were analyzed. The provenance of milk from two dairy cow breeds (Salers and non-Salers) was discussed sensorially and chemically for each cheese sample and for each cheese category. Despite very few significant differences in biochemical parameters, differences were observed concerning the volatile composition and sensory profiles between each cheese category. Salers cheeses were clearly differentiated by their appearance and their more intense aromatic characteristics compared to Cantal cheeses. A large number of volatile compounds (VOCs) belonging to acids, alcohols, aldehydes, ketones and esters were detected in each cheese category (n = 78). The relative quantity of each compound varied depending on the cheese category but was lowly impacted by the origin of the breed’s milk. The results suggest that the provenance of milk (Salers vs. non-Salers) have a low impact on the chemical and sensory differentiation of cheeses regardless of the PDO cheese category. However, the PDO cheese categories (Salers vs. Cantal) were clearly differentiated by their volatile and sensory characteristics. The PDO Salers cheeses presented the highest flavor variability compared to the PDO Cantal cheeses due to compounds belonging to alcohols, acids, aldehydes and ester conferring ammonia, vegetal and animal flavors compared to the PDO Cantal cheeses that were perceived as more pungent and bitter.